A Profile of Aetiological & Therapeutic Searches by Netizen Parents/ Caregivers of Children on the Autism Spectrum - Venkatesan. S; Purushotham K. (Journal of All India Institute of Speech and Hearing)
Autism is a growing tragedy of contemporary information age. A sizeable population of their parents is computer savvy, knowledgeable and active denizens on the new virtual reality available on world-wide web. They spend several hours on the computer keyboard asking questions, seeking answers, sending messages or exchanging notes between themselves or other professionals in virtual chat rooms, internet groups or through personal emails. The present study seeks to empirically profile the frequency, intensity and extensity of thematic concerns/searches by an organized group of internet netizens dedicated to autism. Content analysis of transcripts derived by data mining 3436 email exchanges of the netizens in the studied sample is classified/presented under three heads: (a) spread of information themes/choices; (b) etiology based issues/ transactions; and, (c) themes related to therapy or treatment of individuals with autism. The highest number of discussions center around the theme of therapies/treatments applicable for persons on the autism spectrum (N: 1697; 49.39 %). This is followed by online concerns of the group members on behavior problems or its management (N: 1488; 43.31 %) in their children. Their etiology based explorations cover four categories: (a) Biological; (b) Environmental; (c) Sensory; and, (d) Diet related causes of autism. Content analysis reveals as many as 238 types of treatment related key-words as discussed by members in the internet group. They are classified as nutrition-based, sensory, and education-behavior based therapies, Alternate Medical Systems, biomedical therapies, and Instrument based therapies respectively. The implications of the study are discussed in the context of parental quest for understanding the continuing challenge and enigma called autism.